Health Education and Weight and Height Examination of Grade 3.4.5 Students at SD Negeri 02 Cipagalo, Bandung Regency - Ardayani, Tri; Fauziah, Liliek; Triana, Hanni; Purnasari, Henni (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service research has 2 goals: special and general. The specific purpose is to provide basic health information about menarche and the general purpose is to find out the level of knowledge of female students in grade 3.4.5 at SDN 02 Cipagalo about menarche and to know the weight and height of female students in grade 3.4.5 at SDN 02 Cipagalo. In this community service, an approach method is used that can help in solving existing problems, namely by conducting health examination methods and health counseling. The results obtained are none of the female students were obese in the study of 30 students aged 9–13 years. In addition, the evaluation of the activities showed a significant increase in student knowledge; The percentage of students with sufficient knowledge increased from 32.4% to 51.4%, and the percentage of students with less knowledge decreased from 40.5% to 24.3%. Based on these results, it shows that there is a significant increase in students' knowledge about menarche, with the percentage of students who have sufficient knowledge increasing from 32.4% to 51.4%, and the percentage of students who have less knowledge decreasing from 40.5% to 24.3%. This shows that counseling is effective in increasing students' understanding of important health issues. Also, weight and height were according to age and gender, there was no obesity among the female students.